Differential impact of continuous theta‐burst stimulation over left and right DLPFC on planning. Issue 1 (14th October 2011) - Kaller, Christoph P.; Heinze, Katharina; Frenkel, Annekathrein; Läppchen, Claus H.; Unterrainer, Josef M.; Weiller, Cornelius; Lange, Rüdiger; Rahm, Benjamin
Abstract Most neuroimaging studies on planning report bilateral activations of the dorsolateral prefrontal cortex (dlPFC). Recently, these concurrent activations of left and right dlPFC have been shown to double dissociate with different cognitive demands imposed by the planning task: Higher demands on the extraction of task‐relevant information led to stronger activation in left dlPFC, whereas higher demands on the integration of interdependent information into a coherent action sequence entailed stronger activation of right dlPFC. Here, we used continuous theta‐burst stimulation (cTBS) to investigate the supposed causal structure‐function mapping underlying this double dissociation. Two groups of healthy subjects (left‐lateralized stimulation, n = 26; right‐lateralized stimulation, n = 26) were tested within‐subject on a variant of the Tower of London task following either real cTBS over dlPFC or sham stimulation over posterior parietal cortex. Results revealed that, irrespective of specific task demands, cTBS over left and right dlPFC was associated with a global decrease and increase, respectively, in initial planning times compared to sham stimulation. Moreover, no interaction between task demands and stimulation type (real vs. sham) and/or stimulation side (left vs. right hemisphere) were found. Together, against expectations from previous neuroimaging data, lateralized cTBS did not lead to planning‐parameter specific changes in performance, but instead revealed a global asymmetric pattern of faster versus slower task processing after left versus right cTBS. This global asymmetry in the absence of any task‐parameter specific impact of cTBS suggests that different levels of information processing may span colocalized, but independent axes of functional lateralization in the dlPFC. Hum Brain Mapp, 2013. © 2011 Wiley Periodicals, Inc.